(untitled) (Religious dialogue and cooperation, 2024)
Religious conflicts take place in various ways. This article discusses the role of religions in low-intensity conflicts occurring in people’s daily lives, relationships, and situations. New skills are needed to navigate the mosaic of disputes, rights, and obligations. In addition to ordinary citizens, these skills are needed by professionals in different fields who come across issues and people associated with religions. The article examines the role of the public authorities in encountering issues, problems and conflicts related to religions. While the authorities must safeguard the rights of people belonging to religious movements, they also have to solve problems arising from religions. In the article, the authorities’ activities are explored within the framework of religious literacy. The article discusses the basic principles of religious literacy and the ways in which they are manifested in the context of the authorities’ work. Religious literacy refers interpreting the role of religion in different phenomena, institutions, actors, and interactions in society. Understanding, contextualization and a critical attitude are key components of religious literacy, which could be seen as a professional competence that supports authorities and other employees in their work.